Kekuatan Hukum Memorandum of Understanding (MoU) Dalam Hukum Perjanjian Indonesia - Pratama, Gita Nanda (Faculty of Law, Parahyangan Catholic University, 2016)
AbstractMemorandum of Understanding (MoU), made orally or in written form, is used as the basis for drafting a contract containing elaboration of the parties’ specific rights and duties. MoU may thus be understood as a preliminary agreement to draft a contract. The author, starting from the Indonesian contract law, intend to analyze the extent to which MoU may be considered legally binding by the parties. To that purpose a comparison with how common law system recognize and regulate MoU will be considered necessary. The author’s main argument is that, notwithstanding the fact that there is no rule explicitly recognizing or mentioning the name, MoU’s containing the main understandings reached by parties should be treated as morally binding by the parties.